A Sampling of Canadian Practice in Managing Nonvariceal Upper Gastrointestinal Bleeding before Recent Guideline Publication: Is there Room for Improvement?. (1st August 2005) - Bensoussan, Karen; Fallone, Carlo A; Barkun, Alan N; Martel, Myriam
Abstract : BACKGROUND: There are few recent published consensus guidelines regarding nonvariceal upper gastrointestinal bleeding. In 2003, the Canadian Association of Gastroenterology sponsored a set of 20 recommendations. AIM: To compare current Canadian clinical practice patterns with these most recent guidelines. METHODS: Data obtained from the Canadian Registry of patients with Upper Gastrointestinal Bleeding and Endoscopy (RUGBE), complemented by a questionnaire sent out to the 18 participating RUGBE sites, were used to compare present practice with all 20 guidelines. RESULTS: Only three RUGBE sites had an explicit written protocol for nonvariceal upper gastrointestinal bleeding, and only 40% of the sites had support staff available after hours. The Blatchford prognostic scale was not used routinely, and only one site used the Rockall score for risk stratification. Most patients classified as low-risk according to the literature had endoscopy within 24 h and a median length of stay of two days compared with high-risk patients who underwent endoscopy approximately 4 h earlier, had a median length of stay of 4.3 days and displayed a higher mortality. Nineteen per cent of all patients had a routine second-look endoscopy. Proton pump inhibitors were frequently used in the acute setting. Thirteen per cent of all patients rebled and only 34% of these received a second endoscopy. One-half of all patients were tested for Helicobacter pylori while in hospital, mostly by histology, and one-third of those who tested positive received H pylori eradication during their hospitalization. CONCLUSION: Compared with recommendations put forward in the new guidelines, clinical practice before guideline publication was variable. The future level of guideline adherence and patient outcome data should be quantified and monitored as the guidelines are disseminated.